Postsurgical Diagnosis of an Unusual Case of Primary Hepatic Lymphoma Presenting as Liver Abscess with an Uncommon Complication: A Hepatogastric Fistula - Mbarek Yaka; Farid Chehab; Mohmed Allaoui; Abdelmonaim Ait Ali; Aziz Zentar (Case Reports in Hematology)
Primary hepatic lymphoma (PHL) is a very rare malignancy and constitutes 0.016% of all cases of non-Hodgkin’s lymphoma and 0.4% of extranodal non-Hodgkin’s lymphoma. We describe a rare case of primary hepatic lymphoma presenting as liver abscess which was complicated with the development of a hepatogastric fistula. A 58-year-old man presented with clinical signs of sepsis, high-grade fever, right upper abdominal pain, and weight loss which had progressed in the past 8 months. Noncontrast abdominal computed tomography (CT) revealed a heterogeneously hypodense lesion in the left lobe of the liver with multiple air foci within, which are seen to extend into the body of the stomach. The patient was initially misdiagnosed as a case of rupture of liver abscess into the stomach. Postoperative liver biopsy examination confirmed a diagnosis of diffuse large B-cell lymphoma. Systemic staging revealed no evidence of nodal or bone marrow involvement, so PHL was diagnosed. Chemotherapy was initiated, but discontinued due to the patient’s general condition. Finally, the patient succumbed to neutropenic fever following chemotherapy. Here, we present the exceptional case of a primary hepatic lymphoma with an unusual complication, a hepatogastric fistula, and try through the existing literature to show the difficulties involved in diagnosis and treatment.